Optimal balance between force and velocity differs among world-class athletes - Giroux, C.; Rabita, G.; Chollet, D.; Guilhem, G. (Journal of Applied Biomechanics, 2016)
Performance during human movements is highly related to force and velocity muscle capacities. Those capacities are highly developed in elite athletes practicing power-oriented sports. However, it is still unclear whether the balance between their force and velocity-generating capacities constitutes an optimal profile. In this study, we aimed to determine the effect of elite sport background on the force-velocity relationship in the squat jump, and evaluate the level of optimization of these profiles. Ninetyfive elite athletes in cycling, fencing, taekwondo, and athletic sprinting, and 15 control participants performed squat jumps in 7 loading conditions (range: 0%-60% of the maximal load they were able to lift). Theoretical maximal power (Pm), force (F0), and velocity (v0) were determined from the individual force-velocity relationships. Optimal profiles were assessed by calculating the optimal force (F0th) and velocity (v0th). Athletic sprinters and cyclists produced greater force than the other groups (P < .05). F0 was significantly lower than F0th, and v0 was significantly higher than v0th for female fencers and control participants, and for male athletics sprinters, fencers, and taekwondo practitioners (P < .05). Our study shows that the chronic practice of an activity leads to differently balanced force-velocity profiles. Moreover, the differences between measured and optimal force-velocity profiles raise potential sources of performance improvement in elite athletes.